Evaluation of Photoswitching Properties for Hockey Stick-Shaped Mesogens Bearing Azo Benzene Moieties - Sunil, B. N; Monika, M.; Shanker, Govindaswamy; Hegde, Gurumurthy; Prasad, Veena (Frontiers in Physics, 2021)
In this paper, we report the photoresponsive behavior of hockey stick-shaped mesogens bearing azo wing with different terminal alkoxy chains at one terminal end. Except for the compound E16, which exhibits SmC along with nematic phase, all other mentioned compounds exhibit nematic phase alone. Influence of chain length on the photophysical properties were investigated using UV-Vis spectroscopy. It is observed here that influence of chain length is negligible on thermal back relaxation time. Spectroscopic investigation with variable intensities of UV light studies reveals that reverse cis-trans isomerization process was inversely proportional to the intensity of illuminated light. The present study also reveals that the structure-property relationship plays a dominant role on shape anisotropic structures. A spectroscopic study of the solid sample using guest-host mixture was also carried out and the compilation of results forecast these mesogens as ideal candidates for optical storage devices.